Disassembling and Recomposing.: The Real in the Filmic Image (PHILM. Rivista di filosofia e cinema, 2024)
Starting with an analysis of the concept of constellation in Walter Benjamin’s theory, the aim of this text is to elucidate how montage can be considered a foundational act of art and philosophy in the last century. The majority of the article is devoted to the theory of Russian film director Sergei Ejzenštejn, with a particular focus on his conceptualisation of the image and the value he ascribed to film montage. This article focuses on one of Ejzenštejn’s masterpieces, October, and elucidates the relationship between reality and fiction within the film medium. It demonstrates how the director overcomes this dualism through montage, which is not merely an aesthetic technique but a foundational act.